In vivo examination of enamel microcracks after orthodontic debonding: Is there a need for detailed analysis? - Dumbryte, Irma; Malinauskas, Mangirdas (American journal of orthodontics and dentofacial orthopedics, 2021)
Our aim was to assess changes in the number of enamel microcracks (EMCs) after removing metal brackets in teeth with and without visible EMCs before the bonding procedure. Before bonding, 13 patients having teeth with visible EMCs and 13 subjects whose teeth were free of EMCs were included in the study. All patients were asked to complete a questionnaire with a detailed medical history at the beginning of treatment and after removing metal brackets. The number of teeth with visible EMCs and the number of premolars without EMCs were recorded for each subject twice, that is, before bonding and after debonding, together with the tooth sensitivity assessments elicited by compressed air and cold testing. The number of visible EMCs in premolars increased after removing metal brackets. EMCs were recorded in at least 25.0% of all evaluated teeth for the patients having teeth with and without visible EMCs at the beginning of treatment. However, the changes in the number of visible EMCs were not significantly different (P = 0.619) between the groups. For the subjects with visible EMCs, tooth sensitivity caused by cold was registered nearly 3 times more often after removing brackets compared with the patients without EMCs prior bonding. Formation of EMCs was noticed after debonding. Changes in the number appeared to be similar for the subjects with and without visible EMCs before bonding. Higher incidence of EMCs was associated with more frequent tooth sensitivity perceptions after removing brackets. •New enamel microcracks (EMCs) were noted after debonding in vivo.•There were similar changes in the number of EMCs for patients with and without previous EMCs.•There was a low prognostic value of EMCs' visibility.•A higher incidence of EMCs was associated with more frequent teeth sensitivity.•Compared with in vitro, the tendency of a lower frequency of new EMCs in vivo.